The Impact of Covid-19 on Midwives’ Practice in Kenya, Uganda and Tanzania: A Reflective Account - Pallangyo, Eunice; Nakate , Mary Grace; Maina, Rose; Fleming,Valerie (Midwifery, 2020)
The COVID-19 pandemic has been named as such because the infection is affecting every part of the globe (World Health Organization, 2010). Yet taking account of the daily statistics coordinated by Johns Hopkins University, there have been very few cases reported from East Africa with death rates also relatively low compared with the number of reported cases (Johns Hopkins University, 2020). However, the actions taken by three countries, Kenya, Tanzania and Uganda in response to the pandemic have varied greatly although all have led to maternity service provision being adapted to the individual circumstances of the country concerned. This article provides a brief overview of how the pandemic has affected midwifery practice in each of these three countries, all of which already experience high neonatal and maternal mortality rates (Hug et al., 2019).